Protein and site specificity of fucosylation in liver-secreted glycoproteins - Pompach, Petr; Ashline, David J; Brnakova, Zuzana; Benicky, Julius; Sanda, Miloslav; Goldman, Radoslav (Journal of proteome research, 2014)
Chronic liver diseases are a serious health problem worldwide. One of the frequently reported glycan alterations in liver disease is aberrant fucosylation, which was suggested as a marker for noninvasive serologic monitoring. We present a case study that compares site specific glycoforms of four proteins including haptoglobin, complement factor H, kininogen-1, and hemopexin isolated from the same patient. Our exoglycosidase-assisted LC-MS/MS analysis confirms the high degree of fucosylation of some of the proteins but shows that microheterogeneity is protein- and site-specific. MSn analysis of permethylated detached glycans confirms the presence of LeY glycoforms on haptoglobin, which cannot be detected in hemopexin or complement factor H; all three proteins carry Lewis and H epitopes. Core fucosylation is detectable in only trace amounts in haptoglobin but with confidence on hemopexin and complement factor H, where core fucosylation of the bi-antennary glycans on select glycopeptides reaches 15-20% intensity. These protein-specific differences in fucosylation, observed in proteins isolated from the same patient source, suggest that factors other than up-regulation of enzymatic activity regulate the microheterogeneity of glycoforms. This has implications for selection of candidate proteins for disease monitoring and suggests that site-specific glycoforms have structural determinants, which could lead to functional consequences for specific subsets of proteins or their domains.
Keywords: játra; fucosylation; glycopeptides; mass spectrometry; Humans; lidé středního věku; exoglycosidase treatment; jaterní cirhóza; Molecular Sequence Data; Carbohydrate Conformation; molekulární sekvence - údaje; MSn structural analysis; N-glycans; Hepatitis C; lidé; Liver Cirrhosis; Protein Processing, Post-Translational; posttranslační úpravy proteinů; microheterogeneity; Amino Acid Sequence; glykoproteiny; glykosylace; Liver; hepatitida C; Glycoproteins; Male; Middle Aged; permethylation; hepatocellular carcinoma; Carbohydrate Sequence; sacharidové sekvence; konformace sacharidů; site specificity; mužské pohlaví; Glycosylation; sekvence aminokyselin